ANALISIS PENGARUH CREATIVE PROMOTION, VISUAL MERCHANDISING DAN HARGA PADA KEPUTUSAN PEMBELIAN PRODUK RITEL FASHION (Studi Kasus pada Konsumen PT. Mitra Adi Perkasa) - Nurmalasari, Adellya; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2015)
Abstract Berbahasa Inggris. In this global era, there are big emerging ritail companies in Indonesia. The growing ritail companies in Indonesia caused by the change in consumption patterns, especially in the ritail fashion products. This is supported by the shopping behavior of Indonesian citizen has begun to shift, from shoping in traditional to modern ritail market. This study aims to analyze the influence of creative promotion, visual merchandising, and pricing on product purchasing decisions on consumer ritail fashion of PT Mitra Adiperkasa.The data collection method was collectedÂ by questionnaire . The primary data source used in this study is data on respondent's perceptions of creative promotion, visual merchandising, pricing and purchasing decisions. The questionnaire in this study using a Likert scale. In determining the scale, then we use the measurement scale or range scale. Quantitative analysis includes Validity Test, Reliability Test, Classical Assumption Test, Regression Analysis, and Test of Goodness of Fit which includes analysis coefficient of determination (R2), F test and t test.The results of this study are Creative promotion proved positive and significant impact on purchasing decisions, which can be evidenced from the results of t - test of 2,256. Visual merchandising proved positive and significant impact on purchasing decisions, which can be evidenced from the results of t - test of 4.252. Price proved positive and significant impact on purchasing decisions, which can be evidenced from the results of the test - t of 4.059